2001
DOI: 10.1128/iai.69.3.1895-1901.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alginate O Acetylation in Resistance of MucoidPseudomonas aeruginosato Opsonic Phagocytosis

Abstract: Establishment and maintenance of chronic lung infections with mucoid Pseudomonas aeruginosa in patients with cystic fibrosis (CF) require that the bacteria avoid host defenses. Elaboration of the extracellular, O-acetylated mucoid exopolysaccharide, or alginate, is a major microbial factor in resistance to immune effectors. Here we show that O acetylation of alginate maximizes the resistance of mucoid P. aeruginosa to antibody-independent opsonic killing and is the molecular basis for the resistance of mucoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(190 citation statements)
references
References 48 publications
4
186
0
Order By: Relevance
“…Although these patients are rare (<5% of the total), it has been shown that a high proportion have naturally acquired an antibody to the alginate antigen that is characterized by the antibody's ability to mediate complement-dependent opsonic killing of mucoid P. aeruginosa growing in υitro either as planktonic cells [3,4] or in a biofilm [73]. The antibodies made to alginate by most infected CF patients [3,4], and also by most humans who have natural antibodies to alginate [74], do not mediate efficient opsonic killing because of their specificity for antigenic epitopes on alginate that do not result in deposition of the critical complement opsonin, C3bi, onto the bacterial surface [73]. However, although animal studies indicate there are potential means to induce these opsonically-active antibodies by vaccination [75], this has not readily been achieved in large-scale human trials.…”
Section: Preventing or Limiting The Development Of Infectionmentioning
confidence: 99%
“…Although these patients are rare (<5% of the total), it has been shown that a high proportion have naturally acquired an antibody to the alginate antigen that is characterized by the antibody's ability to mediate complement-dependent opsonic killing of mucoid P. aeruginosa growing in υitro either as planktonic cells [3,4] or in a biofilm [73]. The antibodies made to alginate by most infected CF patients [3,4], and also by most humans who have natural antibodies to alginate [74], do not mediate efficient opsonic killing because of their specificity for antigenic epitopes on alginate that do not result in deposition of the critical complement opsonin, C3bi, onto the bacterial surface [73]. However, although animal studies indicate there are potential means to induce these opsonically-active antibodies by vaccination [75], this has not readily been achieved in large-scale human trials.…”
Section: Preventing or Limiting The Development Of Infectionmentioning
confidence: 99%
“…In the extracellular alginate polysaccharide polymers, produced by isolates of P. aeruginosa from patients with cystic fibrosis, Dmannuronic acid is O-acetylated at O-2 and O-3 by three genes, algI, algJ, and algF (35). Alginate O-acetylation had been shown to contribute to biofilm architecture and microcolony formation (36) and resistance to opsonic phagocytosis (37). OAcetylation is also important for Rhizobium-legume symbiosis.…”
Section: Figmentioning
confidence: 99%
“…aeruginosa can produce a mucoid exopolysaccharide capsule, comprised of alginate, an acetylated random co-polymer of β 1-4 linked D-mannuronic acid (poly-M) and L-guluronic acid (Gacesa & Wusteman, 1990). The overproduction of alginate is believed to play a role in cell adherence within the CF lung and is also thought to be involved in resistance to host defense by reducing susceptibility to phagocytosis (Pier, Coleman, Grout, Franklin, & Ohman, 2001), also in resistance to antibiotics. The small minorities of CF patients, who are carrying only nonmucoid P. aeruginosa, have significantly better lung function over time compared to those patients infected with mucoid P. aeruginosa (Parad, Gerard, Zurakowski, Nichols, & Pier, 1999).…”
Section: Alginatementioning
confidence: 99%